Improving the preoperative care of patients with femoral neck fractures through the development and implementation of a checklist. Issue 1 (5th March 2014) - Agha, Riaz; Edison, Eric; Fowler, Alexander
Abstract: The incidence of femoral neck fractures (FNFs) is expected to rise with life expectancy. It is important to improve the safety of these patients whilst under the care of orthopaedic teams. This study aimed to increase the performance of vital preoperative tasks in patients admitted for femoral neck fracture operations by producing and implementing a checklist as an aide memoir. The checklist was designed primarily for use by senior house officers (SHOs) admitting patients from the emergency department. A list of 12 preoperative tasks was identified. A baseline audit of 10 random patients showed that the mean proportion of the 12 tasks completed was 53% (range 25% - 83%). A survey of 14 nurses and surgeons found that the majority of respondents agreed that there was a problem with the performance of most of the tasks. The tasks were incorporated into a checklist which was refined in three plan-do-study-act cycles and introduced into the femoral neck fracture pathway. In the week following the introduction of the checklist, 77% of the checklist tasks were completed, 24% more than at the baseline audit (53%). In week 3, the completion of checklist tasks rose to 88% and to 95% in week 4. In conclusion, a simple checklist can markedly improve the performance and recording of preoperative tasks by SHOs. We recommend the wider adoption of the new checklist to be produced as a sticker for patients' medical records. Further study is required to ascertain the effect of the checklist on clinical outcomes.